Tigecycline-induced coagulation gene prognostic prediction model and intestinal flora signature in AML - Zhong, Feng-Luan; He, Jia-Jun; Bai, Kun-Hao; Shao, Ruo-Nan; Wu, Guo-Yan; Tian, Xiao-Peng; Wang, Da-Wei; Dai, Yu-Jun; Chen, Si-Liang (Frontiers in Immunology, 2024)
Infection is among the most common causes of death in patients with acute myeloid leukemia (AML) after chemotherapy. The anti-tumor effect of the intestinal microbiota in patients with AML is increasingly being recognized. Tigecycline, a broad-spectrum antibiotics, plays a vital role in the anti-infection treatment of AML patients with neutropenia and accompanying infections. Previously, this group reported that long-term use of tigecycline caused coagulation dysfunction in patients with hematological malignancies, increasing the risk of casualties. RNA sequencing was performed on CHO cells before and after tigecycline treatment. Further, the combined analysis of AML prognostic differentially expressed genes revealed 13 genes affected by tigecycline and closely related to AML prognosis. These genes were used for modeling analysis, and the results showed that the prepared model significantly improved the prognostic prediction efficiency for AML patients. The model also explored the correlation between prognosis score and immune cells infiltrating tumors and immune therapy targets. Moreover, 16S sequencing was performed on fecal samples from AML patients before and after tigecycline treatment. The results revealed that tigecycline significantly altered the distribution of intestinal microbiota in AML patients - These changes in microbiota are related to chemotherapy resistance. This study emphasizes the importance of intestinal microbiota in AML prognosis. Thus, the findings of this study show that the long-term use of antibiotics can not only cause dysbiosis of the intestinal microbiota but also indirectly affect the sensitivity of chemotherapy drugs, affecting the prognosis of AML patients.